(POST-STROKE FATIGUE: PREVALENSI, FAKTOR PREDISPOSISI, DAN STRATEGI PENATALAKSANAAN) - Fadila Hasnadhia; Vitriana Biben; Marietta Shanti Prananta (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Post-stroke fatigue (PSF) is a common and challenging condition that affects 42% to 53% of stroke survivors. It is characterized by persistent exhaustion that does not improve with rest and can significantly affect rehabilitation, daily activities, and overall quality of life. While the exact causes of PSF are not fully understood, various biological and physiological predisposing factors play a role in its onset. Biological factors include age, gender, stroke characteristics, and inflammatory responses, while physiological factors involve comorbidities, pre-stroke fatigue, and sleep disturbances. Psychological aspects, particularly depression and anxiety, are also closely linked to PSF, though their causative role is still debated. Diagnosis relies on subjective assessments, such as fatigue questionnaires, and objective measures, including electromyography (EMG) and electroencephalography (EEG). Management strategies include both pharmacological and non-pharmacological approaches. Dopamine reuptake inhibitors, such as modafinil, have shown potential benefits, whereas selective serotonin reuptake inhibitors, such as fluoxetine, have not demonstrated significant effects. Non-pharmacological approaches offer promising results in fatigue management, including physical exercise, cognitive behavioral therapy, psychoeducation, and transcranial direct current stimulation (tDCS). Given the multifactorial etiology of post-stroke fatigue, a multidisciplinary management strategy is essential. Optimizing recovery requires personalized interventions that combine pharmacological and non-pharmacological therapies tailored to the individual's specific clinical profile. Keywords: post-stroke fatigue, rehabilitation, stroke DOI 10.35990/mk.v9n2.p173-185